High resolution schemes for bluff-body aerodynamics - Nakos, Dimitrios (Cranfield University, 2013)
This MSc by Research study has been conducted with the application of a variety of grid configurations for extensive grid analysis along with various numerical schemes on the Ahmed body benchmark test case, in both 2D and 3D analysis. A number of different numerical schemes were used in conjunction with the Reynolds Averaged Navier – Stokes (RANS) equations for steady state simulations, by implementing the Spalart – Allmaras turbulence model as a closure to the equations. The efficiency of the aforementioned grid – numerical schemes compilation in terms of achieving physically meaningful results is assessed in both commercial, widely – used solvers (FLUENT) and the Cranfield University in – house developed UCNS3D code, ultimately aiming to capture and exhibit the differences in the implementation of similar configurations in different solvers for high resolution methods. The simulation results are analysed further and an extensive conclusion analysis takes place for all the cases examined, with the combination of numerical methods and grid configurations used. It should be pointed here that the purpose of this study is to capture and study the main aspects of the flow in 2D and 3D dimension simulations, as well as the assessment of a compilation of numerical schemes never applied and studied before in the Ahmed body case, in an effort for further insight and physically meaningful results in the case. The aim of this study is not to provide results for effective implementation of the turbulence modelling in the Ahmed body test case.